Comparative Study of Student Apartment’s Facilities: Louvin and Pacific Garden Apartment - Mutiara, Laura Agnes; Harsritanto, Bangun I.R.; Hasan, M. Ismail (MAJ - Malaysia Architectural Journal, 2020)
Housing is one of the basic need of human along with foods and clothes as old Javanese proverb. Every year the demand of housing is getting higher linear to the growth of population. The condition of land limitation has forced housing to grow vertical. The student also demanded the housing near to their university to shorten the campus trip. Nowadays, many developers have built vertical housing near the campus area respond to this demand with several typical student facilities. This research purpose is to compare two student apartments for responding to the typical student space demand in housing. Site observation and internet data compilation were performed to collect data. Literatures review and comparative study were operated to analyse and conclude the research. The results shown the similarity in location and communal facilities, and different approach in the room facilities design.